School for Sustainable Living: Assessing the Energy Related Topics Among Young People - Breskvar, Uros (European Journal of Sustainable Development, 2023)
We associate modern man with a sustainable way of life. The very concept of sustainability is closely linked to the energy we need for our lives. The amount of energy is limited by planet Earth itself and by technology for transformation/capturing energy. Man has always strived to have as much energy as possible, as it significantly affects the quality of life. With a population growth and slowly decreasing reserves of fossil fuels, it is increasingly important to make the most of a given energy and move to clean energy sources. The article conducted research on how well young people know the basic energy values for everyday needs and how familiar they are with current technologies that enable better use of energy. According to the results of the research, suggestions are made for improving general energy literacy among young people. Keywords: energy, sustainable competences, education, knowledge examination